Analysis of Financial Statements in Measuring Financial Performance at PT. Matahari Department Store Tbk - Hidayat, Fadhil; Rifai, Tri Akbar; Utami, Indah Hajar; Sarwinda, Siti; Idris, Hariany (Phinisi Applied Accounting Journal, 2023)
This research is to find out more about PT Matahari Dapartment Store Tbk. As an analysis method, the horizontal analysis method is used. The horizontal financial analysis method examines the same components of financial statements over time. Financial statements under scrutiny are often compared over two or three periods, with the previous period acting as a baseline. In this analysis, the percentage decrease and increase in financial statement items from the previous period are considered.